Sustainable housing development in post apartheid South Africa. - Ramashamole, Bokang (My University, 2011)
The human settlement issue in South Africa has posed a great challenge to the post apartheid government. Due to apartheid, South African human settlements are characterised by spatial separation of residential areas according to class and race; urban sprawl; disparate levels of service provision; low levels of suburban population density; and the concentration of the poor in relatively high-density areas in the urban peripheries and the wealthy in core and intermediate areas. This research report examines the issue of sustainable housing development in post apartheid South Africa. This research report is descriptive in nature as it is intended to understand the impact of housing on sustainable development and also explore the relationship between housing policy and practice. The aim of the research report is examine the impact of housing on sustainable development through a case study analysis of the 2004 Breaking New Ground (BNG) Housing Programme. Housing on this basis can be understood as sustainable housing. BNG is used as a case study programme against the backdrop of the post 1994 housing policy which will be used to probe whether the principal tenets of sustainable development and sustainable housing have been adhered to in the Breaking New Ground Housing Programme. Some of the questions that the research also explores are as follows: what is the importance of sustainable development indicator sets (how sustainability is measured) to housing projects in post-apartheid South Africa; what are the specific concerns that must be addressed, for housing to become sustainable in post apartheid South Africa; what type of infrastructure needs to be put in place for housing to become sustainable; how have financial schemes addressed the problem of affordability?